2014
DOI: 10.3988/jcn.2014.10.3.210
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Korean Version of the Insomnia Severity Index

Abstract: Background and PurposeThe purposes of this study were to standardize and validate a Korean version of the Insomnia Severity Index (ISI-K), and to evaluate its clinical usefulness.MethodsWe translated the ISI into Korean and then translated it back into English to check its accuracy. The 614 patients with sleep disorders who were enrolled in this study comprised 169 with primary insomnia, 133 with comorbid insomnia, and 312 with obstructive sleep apnea. All subjects underwent one night of polysomnography (PSG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
253
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 368 publications
(262 citation statements)
references
References 39 publications
4
253
2
3
Order By: Relevance
“…Lee at al. 22 found that insomnia was more common (35.5%) in patients with OSA compared to 22.8% of the Korean general population 23 and that the presence of insomnia symptom had negative effects on the total scores of SF-36 only in men but not in women. Silva et al 24 showed in their 5-year follow-up study that a longitudinal increase in the difficulty initiating and maintaining sleep was associated with a decline in mental but not physical components of QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Lee at al. 22 found that insomnia was more common (35.5%) in patients with OSA compared to 22.8% of the Korean general population 23 and that the presence of insomnia symptom had negative effects on the total scores of SF-36 only in men but not in women. Silva et al 24 showed in their 5-year follow-up study that a longitudinal increase in the difficulty initiating and maintaining sleep was associated with a decline in mental but not physical components of QoL.…”
Section: Discussionmentioning
confidence: 99%
“…In order to fully characterize POSA and its subtypes, all subjects were asked to complete a series of standardized sleep related and psychometric tests including the Korean version of the Insomnia Severity Index (ISI-K) (Cho et al, 2014), the Pittsburgh Sleep Quality Index (PSQI-K) (Sohn et al, 2012), the Epworth Sleepiness Scale (ESS-K) (Cho et al, 2011), the Beck Depression Inventory-2 (BDI-2-K) (Sung et al, 2008), the Hospital Anxiety and Depression Scale (HADS) (Zigmond and Snaith, 1983), and the Korean version of the Short-Form 36-Item Health Survey (SF-36-K) (Han et al, 2004).…”
Section: Psychometric Testsmentioning
confidence: 99%
“…Participants were asked to complete the Korean version of Insomnia Severity Index (ISI) 18 and Pittsburgh Sleep Quality Inventory (PSQI) 19 based their symptoms during the previous week. The Korean version of the Dysfunctional Beliefs and Attitudes about Sleep, 20 Beck Depression Inventory, 21 and Beck Anxiety Inventory 22 were also administered.…”
Section: Methodsmentioning
confidence: 99%